2014
DOI: 10.3389/fnagi.2014.00027
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular rehabilitation ameliorates chronic dizziness through the SIRT1 axis

Abstract: Dizziness is a common clinical symptom frequently referred to general neurologists and practitioners. Exercise intervention, in the form of vestibular rehabilitation, is known as an effective clinical management for dizziness. This intervention is reported to have a functional role in correcting dizziness, improving gaze stability, retraining balance and gait, and enhancing physical fitness. Dizziness is known to be highly related to inflammation and oxidative stress. SIRT1 is a major molecule for the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Higgins et al 37 have reported that exercise can increase p53 protein expression in lung cancer tumor tissue and induce apoptosis in lung cancer. However, p53 protein expression is suppressed even with exercise training 38 . In addition, in stress-induced mice, despite receiving various kinds of vitamins without considering exercise training, only a tendency of p53 reduction is observed whereas the phosphorylation of p53 is increased by exercise 39 .…”
Section: Discussionmentioning
confidence: 98%
“…Higgins et al 37 have reported that exercise can increase p53 protein expression in lung cancer tumor tissue and induce apoptosis in lung cancer. However, p53 protein expression is suppressed even with exercise training 38 . In addition, in stress-induced mice, despite receiving various kinds of vitamins without considering exercise training, only a tendency of p53 reduction is observed whereas the phosphorylation of p53 is increased by exercise 39 .…”
Section: Discussionmentioning
confidence: 98%
“…The pink-colored chromogen, which was formed by the reaction of 2-TBA with the breakdown products of lipid peroxidation, was measured. [21,35]. NO was detected at concentrations within the range of 10-13 M in the aqueous solution, and the response time was 0.5 s. The analyzer revealed that the concentration of NO was between 10 and 180 IM.…”
Section: Malondialdehyde (Mda) Assaymentioning
confidence: 98%
“…The training consisted of low-impact exercise. The training course and the clinical assessment used to evaluate dizziness severity have been previously described [4,21].…”
Section: Subjects and Exercise Protocolmentioning
confidence: 99%
“…For example Yangkyuk-SanhwaTang, a Chinese herbal formulation, has been shown to reduce both dizziness and levels of pro-inflammatory cytokines TNF-a and IL-6 in Soyangin cerebral infarction patients (Jeong et al, 2002). Kao et al (2014) found that levels of SIRT1, a downregulator of the NF-jB pro-inflammatory pathway, were reduced in patients with chronic dizziness and that vestibular exercise therapy both increased SIRT1 expression and improved dizziness. In addition, several traditional medications for dizziness demonstrate antiinflammatory activity (Huang et al, 2012;Kim et al, 2012;Meng et al, 2009). In summary, there is some evidence to suggest a causal relationship between peripheral inflammation and dizziness, as it appears to be a potential consequence of administration of pro-inflammatory substances.…”
Section: Dizziness and Inflammationmentioning
confidence: 99%